Liquid Chromatography-Mass Spectrometry for the Geographical Sourcing of Cannabis sativa L. - Mariana Fernandes Ramos; Fernanda Rodrigues Salazar; Sabrina Laíz Büttenbender; João A. Coblinski; Mauro Sander Fett; Renata Pereira Limberger; Flávio A. Oliveira Camargo (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics)
Marijuana, dried and ground Cannabis, is the most consumed illicit drug in the world, despite many undesirable and risky effects to human health that are caused by its use. The medicinal use and/or legal recreational use of Cannabis has also been rising worldwide. Therefore, traceability methodologies are increasingly gaining importance whether for forensic use, such as drug trafficking eradication, or for quality control purposes of legal medicinal Cannabis. The goal of this study was to analyze Cannabis samples seized by the Brazilian Federal Police in eradication operations occurred in 2014 and 2017, by means of liquid chromatography-mass spectrometry (LC-MS) and linear discriminant analysis (LDA), aiming to trace their geographical origin. The LDA showed 39.13% accuracy in sourcing the samples from 2014, and 80.95% for the 2017 samples, which indicates that high temperature in the drying step and plant age negatively affect data accuracy.